2012
DOI: 10.7150/jca.4280
|View full text |Cite
|
Sign up to set email alerts
|

Promising Urinary Protein Biomarkers for the Early Detection of Hepatocellular Carcinoma among High-Risk Hepatitis C Virus Egyptian Patients

Abstract: Hepatocellular Carcinoma is a major healthcare problem, representing the third most common cause of cancer-related mortality worldwide. There are 130 million Hepatitis C virus infected patients worldwide who are at a high-risk for developing Hepatocellular Carcinoma. Due to the fact that reliable parameters and/or tools for the early detection of Hepatocellular Carcinoma among high-risk individuals are severely lacking, Hepatocellular Carcinoma patients are always diagnosed at a late stage where surgical solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 60 publications
0
25
0
Order By: Relevance
“…They explained the up-regulated HSP60 in chronic HCV by its anti-apoptotic effect rather than being death-promoting for HCC. 11 Moreover, in HCC group, we found significant positive correlation between HSP60 and CAF-1 (urine and blood) and tumor characters (size, number) and BCLC staging system (p˂0.05), but no significant correlation with AFP could be detected. These finding were in accordance with Li et al and Joo et al, the former documented that CAF-1 over-expression indicated poor HCC prognosis and the later found a strong positive correlation between HSPs and clinic-pathological grading of HCC.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…They explained the up-regulated HSP60 in chronic HCV by its anti-apoptotic effect rather than being death-promoting for HCC. 11 Moreover, in HCC group, we found significant positive correlation between HSP60 and CAF-1 (urine and blood) and tumor characters (size, number) and BCLC staging system (p˂0.05), but no significant correlation with AFP could be detected. These finding were in accordance with Li et al and Joo et al, the former documented that CAF-1 over-expression indicated poor HCC prognosis and the later found a strong positive correlation between HSPs and clinic-pathological grading of HCC.…”
Section: Discussionmentioning
confidence: 84%
“…38 In agreement with our study; Xu et al observed a significant positive correlation between CAF-1 expression and both tumor number and size but 40 In the present study, HSP60 mRNA in urine at cutoff 258354 RU had 85%, sensitivity and 66% specificity for HCC diagnosis, a result agreed with Abdalla and Haj-Ahmad, who found 83% sensitivity and 43% specificity for HSP60 in urine for diagnosis of HCC. 11 Also, HSP60 in blood was able to diagnosis HCC with 85% sensitivity and 60% specificity at cutoff 37576 RU with no supported published data. Regarding urine CAF-1, its sensitivity and specificity for diagnosis of HCC in the current study were 81% and 66% respectively at cutoff 137756 RU.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Currently, the most useful disease markers in urine have been largely for urogenital diseases, such as urothelial cancer [4], renal cell carcinoma [5], prostate cancer [6], and bladder cancer [7]. A few recent studies have demonstrated the feasibility in using urinary proteins as disease markers in distal organs, such as ovarian carcinoma [8], lung cancer [9], hepatocellular carcinoma [10], and gastric cancer [11].…”
Section: Introductionmentioning
confidence: 99%